Strategy essence of development financiallycredit relations in the production - Зінченко, Т. В. (Scientific Progress & Innovations, 2012)
Essence of strategy concept of development financially- credit relations in the production defined as the totality of norms, directions, methods and rules of functioning set on thelong term period in the process of forming, distribution and using financial resources, that will provide the stable functioning of production, its high competitiveness with the purpose of strengthening enterprise position on the market, increases of capacity for a survival in the conditions of market instability. Essence of concepts «strategy», «development» and «financially-credit relations» have been considered. The values of development strategy of financially-credit relations for functioning production have been determined.